2014
DOI: 10.1093/heapol/czu073
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the nature of governance at the level of implementation for health system strengthening: the DIALHS experience

Abstract: Health system governance has been recognized as a critical element of the health system strengthening agenda. To date, health governance research often focuses at national or global levels, adopting a macro-perspective that deals with governance structures, forms and principles. Little attention has been given to a micro-perspective which recognizes the role of health system actors in governance, or to considering the operational level of the health system. This article presents a South African case study of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…Importantly, the complexities and different facets of power dynamics that underwrite attempts towards integrated mental health care are showcased, adding to growing literature on the social mechanisms that influence collaboration. The study confirms and expands on previous studies of the crucial role of health system governance in South African settings, and, importantly, illuminates the role of power in integration and fragmentation of mental health services …”
Section: Resultssupporting
confidence: 84%
“…Importantly, the complexities and different facets of power dynamics that underwrite attempts towards integrated mental health care are showcased, adding to growing literature on the social mechanisms that influence collaboration. The study confirms and expands on previous studies of the crucial role of health system governance in South African settings, and, importantly, illuminates the role of power in integration and fragmentation of mental health services …”
Section: Resultssupporting
confidence: 84%
“…It has also noticed that they do not want to change their organizational culture of violating government rules and regulations. Scott et al (2014) have found through action learning that how the misalignment of organizational configuration, culture and processes affects the governance performance and the findings of the present study were aligned with that of the nature of governance of the orphanage and Zila Parishad.…”
Section: Discussionsupporting
confidence: 82%
“…We also draw on the distinction made by Ortiz Aragon and others ( Fig 2 ) between three interacting dimensions of organisational capacity: the hardware of infrastructure, technology and funding levels; the tangible software of knowledge, skills and processes of decision making; and the intangible software of relationships, communication practices, values and norms. The intangible features have been argued to be particularly important in shaping the behaviours of those working in an organisation and to underpin that organisations’ “power to perform” [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%